Rural development policy in the Ivory Coast - Manfred Schulz (Intereconomics, 1975)
The Ivory Coast has been the scene of a remarkable economic upsurge since it gained independence in 1960. Agriculture and forestry have been the mainstay of growth. The evolvement of socio-economic structures in the rural areas is outlined in the following article which also discusses aspects of the present reorientation of the policy of rural development.
Keywords: 330; Ivory Coast